2019
DOI: 10.1371/journal.pone.0217201
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nurses’ awareness and caring experiences for patients with cervical cancer: A qualitative study

Abstract: To determine the degree to which nurses are aware of cervical cancer and to describe nurses' experiences of caring for patients with cervical cancer. To promote quality of nursing care of cervical cancer, we need to explore their perceptions and nursing experience in doing cervical-cancer care. This study was a qualitative descriptive design. Interviews were conducted with 14 registered nurses. The interviews were audiotaped, transcribed and analyzed. Content analysis was performed. Fourteen nurses who had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
1
0
1
Order By: Relevance
“…The finding of current study revealed that According to the results of the current study's socio demographic features, more than half of the patients in the study group and the control group were between the ages of 30 and 40. These results are reliable and support according to Won Kim H et al, (2019) (19) . stated.…”
Section: Discussionsupporting
confidence: 88%
“…The finding of current study revealed that According to the results of the current study's socio demographic features, more than half of the patients in the study group and the control group were between the ages of 30 and 40. These results are reliable and support according to Won Kim H et al, (2019) (19) . stated.…”
Section: Discussionsupporting
confidence: 88%
“…Among healthcare professionals, several barriers in addressing sexuality exist, for example, feelings of embarrassment, a lack of competence, and time. In a recent Korean qualitative study, 50 one impression was that clinical nurses might have a prejudice about cervical cancer because it is caused by a sexually transmitted disease and the nurses believe that patients with cervical cancer are more difficult to care for than other patients. That impression underscores the need for oncology nurses to receive education, training, and guidance in order to improve their ability to deliver the best care and treatment to patients with cervical cancer.…”
Section: Implications For Practicementioning
confidence: 99%
“…Nurses actively provide information to family and friends of patients about experiences in treating cancer, as well as factors and methods that can prevent cancer to increase family awareness in cancer prevention. 18 According to the family, healthcare professionals can have a supportive influence on families in facing challenges while caring for people with cancer but can also hinder families in facing challenges in caring for people with cancer. 5 This requires communication and building mutual trust between patients and nurses, as well as the family.…”
Section: Discussionmentioning
confidence: 99%